2018
DOI: 10.1021/acssynbio.7b00385
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Artificial Pathway for Efficient Biosynthesis of Hydroxytyrosol

Abstract: Hydroxytyrosol (HT) is a valuable natural phenolic compound with strong antioxidant activity and various physiological and pharmaceutical functions. In this study, we established an artificial pathway for HT biosynthesis. First, efficient enzymes were selected to construct a tyrosol biosynthetic pathway. Aro10 from Saccharomyces cerevisiae was shown to be a better ketoacid decarboxylase than Kivd from Lactococcus lactis for tyrosol production. While knockout of feaB significantly decreased accumulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 40 publications
1
85
2
Order By: Relevance
“…Moreover, when ALR-K was functioning, the levels of DOPA and tyrosol remained minimal showing that the biosynthetic flow from tyrosine to HT was running properly. The negative effect of feaB to remove intermediate metabolites from the introduced pathway to E. coli through AADC and TYR has been shown before [27,28,57], during previous attempts to heterologously produce HT from E. coli, which explains our status of data. Suggested deletion of feaB gene previously resulted in further increase of HT production.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, when ALR-K was functioning, the levels of DOPA and tyrosol remained minimal showing that the biosynthetic flow from tyrosine to HT was running properly. The negative effect of feaB to remove intermediate metabolites from the introduced pathway to E. coli through AADC and TYR has been shown before [27,28,57], during previous attempts to heterologously produce HT from E. coli, which explains our status of data. Suggested deletion of feaB gene previously resulted in further increase of HT production.…”
Section: Discussionmentioning
confidence: 55%
“…The final titer of this metabolic construction was about 22 times higher than that of [27] and 1.3 times higher than that of Chung et al [28] (Table 3), while it was 12 times less than the precursor tyrosine reported to be produced by the tyrosine overproducer strain [29], a fact that dictates space for further optimization. At the time of submission, two new articles drawn our attention for the biosynthesis of hydroxytyrosol in E. coli, authored by Li et al [57] and Choo et al [63]. The performance of their system is of interest due to the efficacy they achieved, especially for the case of Li et al [57] who achieved a titer of 647 mg/L (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping in mind the strongest neuroprotective effect of hydroxyltyrosol, ADH6 gene from S. cerevisiae was overexpressed in the PC12 and PC12+syn + +sep − cell lines to endogenously overproduce hydroxytyrosol from DOPAL and to strengthen the EADS of these cell lines. ADH6 has been previously reported for its efficient catalysis of 3,4-dihydroxyphenylacetaldehyde (DOPAL) into hydroxytyrosol [63,64]. Other studies have also reported the heterologous production of hydroxytyrosol from tyrosol in different bacterial species, such as Pseudomonas aeruginosa, Serratia marcescens, Escherichia coli, and Micrococcus luteus [83].…”
Section: Endogenous Production Of Hydroxytyrosol From Dopalmentioning
confidence: 99%
“…Through a literature survey, we discovered that alcohol dehydrogenase-6 (ADH6) from Saccharomyces cerevisiae catalyzes the conversion of 3,4-dihydroxyphenylacetaldehyde (DOPAL) into hydroxytyrosol with high efficiency [63,64]. DOPAL, an endogenous neurotoxin, is produced from the oxidative deamination of dopamine catalyzed by monoamine oxidases [65].…”
Section: Introductionmentioning
confidence: 99%